Magnetic sense-dependent probabilistic decision-making in humans - Oh, In-Taek; Kim, Soo-Chan; Kim, Yongkuk; Kim, Yong-Hwan; Chae, Kwon-Seok (Frontiers in Neuroscience, 2025)
Even though it is not well characterized how much humans can sense the geomagnetic field (GMF), numerous magnetosensitive animals can detect GMF broadly as a sensory cue, when a spatial decision-making is needed for orientation or migration. In an article of recent series of studies, we showed that the empirical probabilities of stone selections in Go game were significantly different from the theoretical probability. In this study, we assessed the implication of the GMF in modulating subconscious non-spatial decision-making in human subjects and the underlying mechanism with exploiting the zero-sum binary stone selection of Go game as a proof-of-principle. In a laboratory setting, the experimental probability in a decision-making was significantly hampered by the cancelation of the ambient GMF. Moreover, the attenuation of decision-making was confirmed by a specific range of magnetic resonance radiofrequency. In numerous stone selection games among amateur Go players in the artificial magnetic field setting, the analyses of stone selection rate by trials and steps for decision-making pinpointed the subconscious stone selection as a primary modulating target in the binary decision-making. Our findings may provide unique insights into the impact of sensing GMF in probabilistic decision-making in which theoretical probability is manifested into empirical probability through a magnetic field resonance-dependent mechanism.